Liquid levothyroxine formulations in patients taking drugs interfering with L-T4 absorption - Gatta, Elisa; Bambini, Francesca; Buoso, Caterina; Gava, Maria; Maltese, Virginia; Anelli, Valentina; Delbarba, Andrea; Pirola, Ilenia; Cappelli, Carlo (Frontiers in Endocrinology, 2022)
Purpose To describe the current knowledge on thyroid hormonal profile in patients on liquid L-T4 therapy and drugs known to interfere with L-T4 absorption. Methods A PubMed/MEDLINE, Web of Science, and Scopus research was performed. Case reports, case series, original studies and reviews written in English and published online up to 31 August 2022 were selected and reviewed. The final reference list was defined based on the relevance of each paper to the scope of this review. Results The available data showed that novel levothyroxine formulations circumvent gastric pH impairment due to multiple interfering drugs such as proton pump inhibitors, calcium or iron supplements, sevelamer, aluminum/magnesium hydroxide and sodium alginate. Conclusion New formulations can be taken simultaneously with drugs interfering with L-T4 absorption, in particular liquid formulations. Softgel capsules need more studies to support these data.